Comparison of the bronchodilating effects of albuterol delivered by valved vs. non-valved spacers in pediatric asthma (2012)
Inhaled therapy using a metered‐dose inhaler (MDI ) with attached valved holding chamber has been increasingly recognized as the optimal method for delivering bronchodilators for asthma treatment. However, mainly due to the high cost of these valved holding chambers in many developing countries, the use of non‐valved spacers is frequent, despite the scarce evidence that supports their efficacy. The aim of this study was to compare the bronchodilator response to albuterol administered by MDI with and without a valved spacer. In a randomized, two‐period, two‐sequence crossover clinical trial, we analyzed 31 stable asthmatic children (6–18 yrs of age) on two consecutive days, who were randomly assigned to receive 100 μg of albuterol MDI through either a locally produced valved spacer or a non‐valved spacer. The next day, a crossover treatment was employed through the use of the other spacer. Spirometry was recorded before and after each albuterol administration. As we were not able to identify any sequence or carryover effect, we tested for treatment effects in both periods. No significant differences in the absolute change in FEV 1 (0.20 ± 0.17 vs. 0.18 ± 0.16, p = 0.63), FVC (0.07 ± 0.13 vs. 0.07 ± 0.16, p = 0.88), or MMEF (0.49 ± 0.31 vs. 0.43 ± 0.39, p = 0.53) after bronchodilator administration were found between the use of valved and non‐valved spacers. In stable asthmatic children, albuterol administered through MDI using a non‐valved spacer produces a bronchodilator response similar to that of a spacer with a valve that requires an inhalatory opening pressure (with flows between 2 and 32 l/min) that even toddlers with bronchial obstruction can easily generate.